ANALISA SENYAWA BIOAKTIF ANTIOKSIDAN DAN ZAT GIZI TERHADAP BUAH TERUNG POKAK (Solanum torvum) SEBAGAI BAHAN PANGAN FUNGSIONAL - Nunuk Helilusiatiningsih; Edy Soenyoto Soenyoto (BUANA SAINS, 2020)
Solanum torvum has potential as a functional food ingredient because it contains bioactive antioxidant compounds which are quite high and are proven as herbal medicines in China and are a popular food in Florida, Alabama, West India, Malaysia, Thailand, Mexico, Central America, South America, Brazil. The study aims to analyze the components of bioactive antioxidant compounds and nutrients in qualitative and quantitative methods and functional groups in fresh Solanum torvum. The research method used phytochemical screening, quantitative tests, chemical identification with LCMS, FTIR, AAS. The results of phytochemical screening studies, the Solanum torvum contains few alkaloids, while it contains a great number of saponins, steroids, glycosides. The quantitative test showed that the fruit contains 36.31 mg /g phenol, 0.62 mg/g tannin content, 2.76 mg/g flavonoid content and antioxidant activity (% DPPH inhibition) of 84.55%, 82.77% water content, 1.63% ash content, 2.73% fat content,  9.78% protein, 3.69% carbohydrates, 3.77% vitamin C, 0.97% phosphorus, 0.13% potassium, Ca 36.64 ppm, Mg 79.1 ppm, Fe 2.34 ppm. Chemical tests with LCMS contain 13 types of components namely (1) chlorogenic acid, (2) 4-O-caffeoylquinic, (3) 3-O-caffeoylquinic, (4) 4-O-caffeoylquinic, (5) 3-O-feruloylquinic acid, (6) 5-O-feruloylquinic acid, (7) 3-O-dicaffeoylquinic acid, (8) 4-O-dicaffeoylquinic acid, (9) 3-5-O-dicaffeoylquinic acid, (10) 3-O -feruloylquinic acid, (11) 5-O-feruloquinic acid, (12) putative dicaffeoylquiniacid, (13) putativedicaffeoylquinic acid. The functional groups of Solanum torvum have seven types namely phenol (OH), Alkane (C-H), Alkene (C = C), aromatic ring, Nitro (NO2), Amine and Amide (C-N), Alcohol (C-O). Thus, fresh Solanum torvum contains potential antioxidant compounds and nutrients that function for health and functional food.